Solitary Submandibular Schwannoma Mimicking a Salivary Gland Tumor in a Child - Kim Yew Richard WONG; Ikram HAKIM; Halimuddin SAWALI; Rachel Cui Ai LIM; Nur Kamilia MOHD MOHSIN (Medeniyet Medical Journal)
Tumors occurring in the submandibular space are infrequent among pediatric patients, and benign peripheral nerve tumors in this region are exceptionally rare. This study describes the uncommon occurrence of a schwannoma in the submandibular space in a child and describes its management. A 7-year-old child presented with a gradually enlarging swelling over a 7-month period in the submandibular region, clinically resembling a salivary gland tumor. There were no associated marginal mandibular, lingual, or hypoglossal nerve palsy. The mass was excised completely, and histopathological examination revealed it to be a schwannoma. It is appropriate to consider benign peripheral nerve tumors, such as schwannoma, in the differential diagnosis of submandibular space tumors in children.